2014
DOI: 10.5539/sar.v3n1p76
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Involvement in Nonfarm Income Generating Activities Among Local Farmers: The Case of Ughelli South Local Government Area of Delta State, Nigeria

Abstract: The study investigated the factors influencing the involvement of farm families in non farm income generating activities. Multi -stage and stratified simple random sampling procedures were used to compose the sample. The sample was made up of seventy two (72) heads of rural farm families. Data were collected by use of structured interview schedule and Focus Group Discussion. Data were analysed by simple percentage, Chi square test, multiple regression and correlation There was a significant relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
4
9
1
2
Order By: Relevance
“…Similar result was reported by [26] and [27] that trading was the most participated non-farm income generating activities among farmers and rural dwellers respectively. These findings support the views of [28]; [29]; [26]; [1] and [30] that even though farming is the predominant activity in most rural areas, rural dwellers usually engage in non-farm income generating activities. Majority (41.70%) of rural youth had low involvement in non-agricultural income generating activities (Table 4).…”
Section: Resultssupporting
confidence: 91%
“…Similar result was reported by [26] and [27] that trading was the most participated non-farm income generating activities among farmers and rural dwellers respectively. These findings support the views of [28]; [29]; [26]; [1] and [30] that even though farming is the predominant activity in most rural areas, rural dwellers usually engage in non-farm income generating activities. Majority (41.70%) of rural youth had low involvement in non-agricultural income generating activities (Table 4).…”
Section: Resultssupporting
confidence: 91%
“…The findings are supported by Oladeji (2007) Sheheli (2012) argued that in Bangladesh rural women even involved in 11 types of livelihood activities. Simmilar type of findings were also reported by Ovwigho (2014) andUmunnakwe et al, (2014Bennell (2010) opined that rural youths involve in different activities for livelihood. The general picture emerging from the analysis is that rural male youths were practising diversified livelihood activities in the surveyed area.…”
Section: Resultssupporting
confidence: 61%
“…Okoye (1995); CPD (2004); Oladeji (2007); Sheheli (2012) and Ovwigho (2014) affirm that even though farming is the predominant activity in most rural areas, rural dwellers usually engage in non-farm income generating activities. The findings support the view of Bennell (2010) who opined that rural youth are engaged in a diverse range of productive activities both agricultural and non-agricultural which make up their livelihood strategies.…”
Section: Resultsmentioning
confidence: 99%
“…This scenario undoubtedly prompts young members of these households to participate in livelihood activities. Binkadakatti (2013) concluded that family size has positive and significant relationship with livelihood security of rehabilitant farmers while Ovwigho (2014) found that household size has positive association with income generating activities of farmers. Inter-correlation of socio-personal characteristics revealed that caste of the respondents was negatively related to their marital status.…”
Section: Resultsmentioning
confidence: 99%